Optimal design of net zero energy residential buildings in tropical climate - Sharif, Hafiz Zafar (2021)
The building sector is the largest consumer of energy worldwide and puts substantial pressure on primary energy sources. The residential buildings in Malaysia consume 21.25 % of total electricity generation due to the hot and humid climate, which enforces massive air conditioning systems. Net Zero Energy Residential Buildings (NZERBs) are an acceptable solution to reduce pressure on the primary sources of energy. Still, it is challenging to design an NZERB of low BEI and small PV systems in a tropical climate. This study aimed to design NZERB in a tropical climate and optimized Building Energy Intensity ≤ 80 kWh/m2/year. In the first step, simulation tools sufficient accuracy validated by a comparative study between the predicted and actual energy consumption of experimentally verified NZERB in Muscat. For, base-case building design as per IECC-2015, energy simulation tool HAP predicted BEI of 147.72 kWh/m2/year and PVWatts calculator estimated 28 kW PV system to balance the energy demand. Two optimization approaches, Taguchi Orthogonal Arrays and RSM-Box-Behnken used in this study. Taguchi Orthogonal approach used for the selection of the most influential factors due to its less computing time. After identifying significant factors, RSM-Box-Behnken technique with Design-Expert tool used to develop the prescriptive path requirements to design NZERB in a tropical climate. For optimal building design, energy simulation tool HAP predicted BEI of 67.085 kWh/m2/year (54% smaller), and PVWatts calculator predicted 13 kW system (53.57% smaller), as compared to the base-case building design. These results suggest that selected methodology to design and optimized NZERBs has sufficient accuracy and results of prescriptive path requirements are reliable to design NZERBs in a tropical climate without energy modelling.